If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + 2(t + 8) = 0 Reorder the terms: 5t + 2(8 + t) = 0 5t + (8 * 2 + t * 2) = 0 5t + (16 + 2t) = 0 Reorder the terms: 16 + 5t + 2t = 0 Combine like terms: 5t + 2t = 7t 16 + 7t = 0 Solving 16 + 7t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 7t = 0 + -16 Combine like terms: 16 + -16 = 0 0 + 7t = 0 + -16 7t = 0 + -16 Combine like terms: 0 + -16 = -16 7t = -16 Divide each side by '7'. t = -2.285714286 Simplifying t = -2.285714286
| 2(x-4)+8=3x-8+2x | | -5=4h-15 | | 2(x-4)+8=8x+2x | | 5-3(2x-1)=2x+4 | | 3x-(-x)+2y= | | 4(a-7)+8=2(a-4) | | -6p+4p=4(1+2p)-8(2p+5) | | 4x+5x=6x | | 0.9x-0.5(5-x)=6.6 | | X(3x)=486 | | 4x+7=-30 | | -7+8=3 | | 9x+4=2x+32 | | 0.015w-1.85=1.615 | | -4(2t+8)=-8 | | -2(-7n-8)-8n=6(n-6) | | 8z+4-5z=44-5 | | 12x-2(6x-10)=1 | | g(x)=x-25x^3 | | x+36-12=42 | | 4y-12=2x | | -5(v+1)+5(1-7v)=4v+4v | | 8z+4+5z=44-5z | | -2(7n-8)-8n=6(n-6) | | -1x-7=18 | | 3(x^2+4x-1)=0 | | -20+2y=-22 | | 18+2x-12=42 | | 4(f-3)=-4 | | 2(y-1)+y=37 | | -6+14x=36 | | 10(s-6)=-129 |